Kepemimpinan Dalam Pembentukan Blimbingsari Menjadi Desa Wisata - I Wayan Ruspendi Junaedi (Universitas Kristen Wira Wacana Sumba, 2014)
Government programs in the field of tourism planning seven million tourists visited Indonesia and at least four million of which visit the island of Bali in 2013. Mrs. Wendy, a stranger from Australia ever stayed in Blimbingsari said: